Effect of Concrete-Steel Interactions on the Performance of Emended Distributed Optical Fiber Sensor - ALhamad A.M.; Mohammed Y.; Hayder G. (Springer Nature, 2024)
Distributed optical fiber sensor (OFS) is a cutting-edge technology that has been introduced to the construction industry as a structural health monitoring system for the structural assessment of existing and newly built structures. The OFS can be attached to the surface of the existing structures or embedded into the newly built structures. Furthermore, the bond stress resistance produces the composite action at the embedded reinforcement and the adjoining concrete interfaces. This study is developed to determine the effects of the interaction at the interfaces and their impact on the performance of the distributed OFS as a monitoring system of the structural health. The strain evolution will be obtained from the previous study and used with different perspectives compared to the original research. Therefore, monotonic loading was applied in terms of displacement control with roller supports to obtain the maximum strain profile of the reinforced concrete beam. The result obtained will be used to develop the relationship of the bond-slip and compare it with Model Code 2010 predicated bond-slip relationship. Therefore, the bond-slip relationship is significant concern to evaluate the impact of the concrete-to-steel interaction on the OFS performance. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.